2010
DOI: 10.3109/03639040903225109
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Raman spectroscopy as PAT tool in active coating

Abstract: Raman spectroscopy is an appropriate process analytical technology too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…• To monitor the effect of compression weight on API properties [187] • To monitor the effect of compression pressure on API properties [188] • To monitor the quality of tablets during compression [189] • To monitor tablet-to-tablet coating variability [190] • To monitor the uniformity of active ingredients in coating layer [191] • To monitor coating thickness on tablets during pan-coating process [192] Figure 2. Examples of application of Raman spectroscopy during online monitoring of various steps involved in tabletting process are shown [175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192].…”
Section: Coatingmentioning
confidence: 99%
“…• To monitor the effect of compression weight on API properties [187] • To monitor the effect of compression pressure on API properties [188] • To monitor the quality of tablets during compression [189] • To monitor tablet-to-tablet coating variability [190] • To monitor the uniformity of active ingredients in coating layer [191] • To monitor coating thickness on tablets during pan-coating process [192] Figure 2. Examples of application of Raman spectroscopy during online monitoring of various steps involved in tabletting process are shown [175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192].…”
Section: Coatingmentioning
confidence: 99%
“…Much of the previous work has focused on methods for measuring the coating thickness on a tablet using techniques such as direct film thickness measurements (Wilson and Crossman, 1997), near-infrared spectroscopy (Pé rez-Ramos, 2007), terahertz imaging (Taday, 2008), laser induced breakdown spectroscopy (Madamba et al, 2007), and Raman spectroscopy (Müller et al, 2010). These tools have shown that the coating thickness can vary widely over a tablet's surface.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, process understanding is increasing steadily through advances in the field of modelling film coating on the process scale 3,4 as well as understanding the physicochemical changes of the film formation itself on the micro scale. 5,6 In order to reduce process time and improve the quality of the coating process, a number of optical sensors, for example, at near-infrared frequencies 7,8 or using Raman spectroscopy, 9,10 have been developed previously to monitor the coating operation and to determine the process endpoint. Conceptually, both of these techniques measure the coating thickness indirectly in that they either track the attenuation of the spectral features of one of the constituents, which is exclusive to the tablet core matrix, or the buildup in intensity of the spectral features in a component that is only found in the coating formulation but not in the tablet core.…”
Section: Introductionmentioning
confidence: 99%